Expression and Characterization of Xyloglucanase from Paenibacillus borealis and Its Application in the Production of Xylogluco-oligosaccharides from Apple Pomace - Jiaxin TIAN; Hang YANG; Yuqi ZHAO; Qiaojuan YAN; Yanxiao LI; Zhengqiang JIANG (Shipin gongye ke-ji)
Apple pomace (AP) is rich in xyloglucan, serves as a substrate to produce xylogluco-oligosaccharides with various functional activities. The hydrolysis of AP by novel xyloglucanases is conducive to the high-value utilization of AP. In this study, a novel GH74 xyloglucanase gene (PbXEG74B) from Paenibacillus borealis was cloned and expressed in Escherichia coli BL21 (DE3). The enzyme was characterized and further used to hydrolyze AP for xylogluco-oligosaccharides production. It was expressed in E. coli with an expression level of 18.0 U/mL. The optimal conditions of PbXEG74B were pH5.5 and 55 ℃. It showed good stability in the pH range of 4.5~8.5 and temperatures up to 40 ℃. The enzyme hydrolyzed xyloglucan to produce xylogluco-oligosaccharides with degrees of polymerization (DP) of 2~9. AP was pretreated with deep eutectic solvents (DESs) and hydrolyzed by PbXEG74B to produce xylogluco-oligosaccharides. Under optimal conditions, the yield of xylogluco-oligosaccharides with DP 2~9 was 2.79 g/100 g AP, containing 67.0%, 11.5%, and 21.5% of xylogluco-oligosaccharides with DP 2~4, 5~6, and 7~9, respectively. PbXEG74B with good enzymatic and hydrolytic properties shows great potential in the high value utilization of AP.